Promises and potential pitfalls of long-acting injectable pre-exposure prophylaxis - Carey Pike; Elzette Rousseau; Linda-Gail Bekker (AOSIS, 2023)
The number of products that can provide pre-exposure prophylaxis (PrEP) for HIV prevention is expanding, with three now approved in South Africa (oral Tenofovir-based PrEP, injectable Cabotegravir, and a Dapivirine-based vaginal ring) and more in the development pipeline. Although highly effective and safe, oral PrEP products have not reduced HIV incidence in South Africa to the extent seen in other countries, primarily due to adherence challenges, rapidly diminishing persistence over time, and insufficient scale-up of PrEP service delivery. The Dapivirine vaginal ring, which provides 1-month-long protection, provides women with a new and discreet choice for PrEP; however, it is Cabotegravir long-acting (CAB LA) that is anticipated to land the largest impact. Administered as an intramuscular injection given every 2 months, CAB LA is safe, highly efficacious, and expected to become available in South Africa in late 2023. Yet, clinical and implementation questions remain, including the need to understand and characterise breakthrough HIV infections amongst CAB LA users, knowledge of how to package each PrEP product in a new context of PrEP choice, and how to avoid the remedicalisation of PrEP access following extensive efforts to make oral PrEP delivery differentiated and community based.